2022
DOI: 10.1159/000526804
|View full text |Cite
|
Sign up to set email alerts
|

Letter Regarding “Impact of Immune-Related Adverse Events on Efficacy of Immune Checkpoint Inhibitors in Patients with Advanced Hepatocellular Carcinoma”

Abstract: Immunologic checkpoint inhibitors (ICIs) have demonstrated efficacy in a variety of malignancies. Despite impressive therapeutic benefits, ICIs may induce profound immune-related adverse events (irAEs). While the occurrence of irAEs may implicate improved T cell activity, whether irAEs predicts anti-tumor immune responses remains controversial. The paper by Kennedy Yao Yi Ng et al. adds to the evidence of the impact of irAEs in advanced hepatocellular carcinoma, which demonstrated that multi-system involvement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
(18 reference statements)
0
1
0
Order By: Relevance
“…Another study involving 198 patients undergoing ICIs treatment found that the occurrence of grade ≥3 irAEs was associated with better survival compared to grades 1 and 2 (PFS: 8.5 months vs. 3.6 months vs. 1.3 months; OS: 26.9 months vs. 14.0 months vs. 4.6 months) (160). However, some concerns have been raised by other researchers regarding the grouping and statistical analysis methods employed in this study (161). Furthermore, in a multicenter study involving 268 patients treated with Atez/Bev, no significant differences were found in OS and PFS concerning irAEs (69).…”
Section: Immune-related Adverse Eventsmentioning
confidence: 82%
“…Another study involving 198 patients undergoing ICIs treatment found that the occurrence of grade ≥3 irAEs was associated with better survival compared to grades 1 and 2 (PFS: 8.5 months vs. 3.6 months vs. 1.3 months; OS: 26.9 months vs. 14.0 months vs. 4.6 months) (160). However, some concerns have been raised by other researchers regarding the grouping and statistical analysis methods employed in this study (161). Furthermore, in a multicenter study involving 268 patients treated with Atez/Bev, no significant differences were found in OS and PFS concerning irAEs (69).…”
Section: Immune-related Adverse Eventsmentioning
confidence: 82%